Pressure and velocity measurements of an incompressible moderate Reynolds number jet interacting with a tangential flat plate. (31st March 2015) - Di Marco, A.; Mancinelli, M.; Camussi, R.
Abstract : The statistical properties of wall pressure fluctuations generated on a rigid flat plate by a tangential incompressible single stream jet are investigated experimentally. The study is carried out at moderate Reynolds number and for different distances between the nozzle axis and the flat plate. The overall aerodynamic behaviour is described through hot wire anemometer measurements, providing the effect of the plate on the mean and fluctuating velocity. The pressure field acting on the flat plate was measured by cavity-mounted microphones, providing point-wise pressure signals in the stream-wise and span-wise directions. Statistics of the wall pressure fluctuations are determined in terms of time-domain and Fourier-domain quantities and a parametric analysis is conducted in terms of the main geometrical length scales. Possible scaling laws of auto-spectra and coherence functions are presented and implications for theoretical modelling are discussed.